The Implementation Of Murabahah Financing Contracts In Bank Syariah Indonesia - Supriyandi Supriyandi; Saiful Anwar (Jurnal Ilmiah Ekonomi Islam, 2023)
One of the Bank Syariah Indonesia branches, Bank Syariah Indonesia Parepare, engages in buying, selling, and profit-sharing financing activities (Murabahah and Musyarakah). In order to implement Murabahah contracts in Bank Syariah Indonesia Parepare, provisions and norms must be understood and identified. Because the lending institution offers a commercial product, sharia financing via a Murabahah contract, this research was carried out at Bank Syariah Indonesia Parepare. The methodology employed in this study is a qualitative strategy that involves making direct observations, gathering numerous documents, and holding meetings with Bank Syariah Indonesia Parepare officials, workers, and customers to be interviewed. Data reduction, presentation, and conclusion-drawing processes were used to analyze research data in stages. The findings of this study indicated that there is still a lack of consistency from the government and banks in socializing and making policies related to the existence of Bank Syariah Indonesia, a lack of public awareness of the existence of Bank Syariah Indonesia as a result of a lack of knowledge about sharia financing, as well as a lack of knowledge and understanding of sharia bank officers regarding the mechanisms and provisions of Islamic financial institutions.